Expansion and Paraphrase Strategies of Slang Words in Teen Movies: A Translation Analysis - Arshila Andista Mantika; Ichwan Suyudi (E-Structural (English Studies on Translation, Culture, Literature, and Linguistics), 2023)
Abstract. The aims of this study are to identify the types of slang word formation using Yule’s (2019) theory and to investigate the subtitling strategies of expansion and paraphrase employed by translators in translating slang words using Gottlieb’s (1992) theory. The data used in this research are slang words in English subtitles and their Indonesian translations in the movie Work It, Moxie, and He's All That. Moreover, the researchers used the descriptive qualitative method. As a result, the researchers found that there were 80 data found from the three movies. The researchers found that only 6 word-formations were identified in the three movie subtitles. The word formations were coinage, compounding, clipping, derivation, conversion, and multiple processes. Furthermore, the researchers found that there were only 3 data from the three movies that applied the expansion strategy. Meanwhile, there were 77 data from the three movies that applied the paraphrase strategy. The results indicate that the paraphrase strategy is frequently employed because most of the slang words used in movies is required generalization, modification, and alteration to be understood by the target audience.Keywords: expansion strategy; paraphrase strategy; slang; subtitling strategy; word formationAbstrak. Tujuan dari penelitian ini adalah untuk mengidentifikasi jenis-jenis pembentukan kata slang menggunakan teori Yule (2019) dan untuk menyelidiki strategi takarir, yaitu strategi expansi dan parafrasa yang digunakan oleh penerjemah dalam menerjemahkan kata-kata slang menggunakan teori Gottlieb (1992). Data yang digunakan dalam penelitian ini adalah kata-kata slang dalam takarir bahasa Inggris dan terjemahan bahasa Indonesianya dalam film Work It, Moxie, dan He's All That. Selain itu, peneliti menggunakan metode deskriptif kualitatif. Hasilnya, peneliti menemukan ada 80 data yang ditemukan dari ketiga film tersebut. Peneliti menemukan bahwa hanya 6 pembentukan kata yang diidentifikasi dalam tiga film. Pembentukan kata tersebut yaitu coinage, compounding, clipping, derivation, conversion, dan multiple processes. Selanjutnya peneliti menemukan bahwa hanya ada 3 data dari ketiga film yang menerapkan strategi ekspansi. Sementara itu, terdapat 77 data dari tiga film yang menerapkan strategi parafrasa. Hasil penelitian menunjukkan bahwa strategi parafrasa sering digunakan karena kebanyakan kata slang yang digunakan dalam film memerlukan generalisasi, modifikasi, dan perubahan agar dapat dipahami oleh khalayak sasaran.Kata kunci: pembentukan kata; slang; strategi ekspansi; strategi parafrasa; strategi subtitling